1981
DOI: 10.1007/bf00253406
|View full text |Cite
|
Sign up to set email alerts
|

Increased kidney size, glomerular filtration rate and renal plasma flow in short-term insulin-dependent diabetics

Abstract: Summary. Glomerular filtration rate (GFR), renal plasma flow (RPF) and kidney volume were measured in thirteen male subjects (mean age 30 years) with short-term insulin-dependent diabetes (mean duration of disease 2.4 years) and fourteen normal male subjects (mean age 29 years). GFR and RPF were measured by constant infusion technique using I125-iothalamate and 13q-hippuran. Kidney size was determined by means of ultrasound. GFR, RPF and kidney volume were increased in the diabetic patients compared to the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
148
2
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(167 citation statements)
references
References 24 publications
15
148
2
2
Order By: Relevance
“…Correlations between size and function have been found in adults with hypertension or renal disease using urography (46), in diabetics (1,38) and elderly hospitalized patients (47) using sonography, and in disease-free cancer patients using CT scanning (23). However, no correlation was found between sonographic kidney size and GFR in normal subjects (38). Our data show that there is a strong relationship between renal parenchymal volume and GFR and that this correlation remained highly significant when age, gender, race, and body size were taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between size and function have been found in adults with hypertension or renal disease using urography (46), in diabetics (1,38) and elderly hospitalized patients (47) using sonography, and in disease-free cancer patients using CT scanning (23). However, no correlation was found between sonographic kidney size and GFR in normal subjects (38). Our data show that there is a strong relationship between renal parenchymal volume and GFR and that this correlation remained highly significant when age, gender, race, and body size were taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperfunctional kidney with increase in GFR is reported in the early stages of diabetes [19]. Long term metabolic control is known to reduce kidney filtration in human diabetic subjects [20].…”
Section: Discussionmentioning
confidence: 99%
“…Albumin excretion was increased to the same extent in the sorbinil-treated and in the untreated diabetic rats. We conclude that increased metabolism of glucose to sorbitol does not cause the hyperfiltration in rats with streptozotocin-induced diabetes.Key words: Streptozotocin diabetic rat, aldose reductase inhibition, glomerular filtration rate, ultrafiltration pressure, albuminuria.Glomerular hyperfiltration, intrarenal hypertension and kidney enlargement are typical findings in the early stage of human Type 1 (insulin-dependent) diabetes mellitus as well as in experimental diabetes [1][2][3][4]. It has been shown that in experimental diabetes, elevations in single nephron glomerular filtration rate (SNGFR) result from concomitant elevations in ultrafiltration pressure and glomerular plasma flow [5].…”
mentioning
confidence: 99%
“…Glomerular hyperfiltration, intrarenal hypertension and kidney enlargement are typical findings in the early stage of human Type 1 (insulin-dependent) diabetes mellitus as well as in experimental diabetes [1][2][3][4]. It has been shown that in experimental diabetes, elevations in single nephron glomerular filtration rate (SNGFR) result from concomitant elevations in ultrafiltration pressure and glomerular plasma flow [5].…”
mentioning
confidence: 99%